Some Aspects Of Nephrotoxicity Of Most Used Nonsteroidal Anti Inflammatory Drugs In Patients With Degenerative Spondyloarthropathy - Dejan Spasovski; Sonja Genadieva-Stavric; Slavica Subevska-Stratrova (My University, 2020)
Objectives: To determine the effect of initial therapy with Acetaminophen and Ketoprofen on glomerular and tubular integrity in degenerative spondyloarthropaty (DSA), to quantify nephrotoxicity of these two drugs by measurement of enzymuria, which correlates with the damage of tubular epithelium. Microalbuminuria is used as a marker for glomerular damage, and urine excretion of N-Acetyl-−D-glucosaminidase (NAG) as an indicator of proximal tubular damage. Material and Methods: Using colorimetric method for determination of NAG, and immunoturbidimetric method for microalbuminuria, samples of 70 participants were examined (35 DSA patients treated with Acetaminophen only, 35 DSA pa - tients treated with Ketoprofen). The follow up was in 5 time-intervals in the course of 24 weeks. Results: There was a moderate correlation between NAG and microalbuminuria (r=0,16) in the group of patients treated with Acetaminophen only, and a moderate correlation (r=0,28) in the group of patients treated with Ketoprofen. NAG enzymuria in size, number of patients registered, and time of appearance, were greater and appeared earlier in the Ketoprofen group compared to the Acetaminophen group. Conclusion: Ketoprofen is more potent NAG inductor and provokes greater tubular enzymuriathan Acetaminophen. Results from our study confirm safety in use of Acetaminophen and Ketoprofen in everyday clinical practice.
Keywords: N-acetyl-b-D-glucosaminidase; microalbumin; Spondyloarthropaty; Acetaminophen; Ketoprofen